1995
DOI: 10.1159/000159084
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Elastin Peptides on Vascular Tone

Abstract: Elastin peptides are present in human blood. As elastin receptors exist on several cell types, especially endothelial cells, this investigation was carried out to study the effect of elastin peptides on vascular tone. For this purpose, rat aortic rings were mounted in an organ bath for isometric tension measurements. Elastin peptides (ĸ-elastin) were added in the concentration range of 0.1 ng/ml to 1 µg/ml, concentrations similar to those found in the circulating blood. In rat aortic rings, precontracted or no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0
3

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(71 citation statements)
references
References 19 publications
3
60
0
3
Order By: Relevance
“…We, and others, show that interaction between elastin-derived peptides and EBP residing on the surface of several cell types results in a rapid and transient increase in free intracellular Ca 2ϩ (18,36) and that the EBP-mediated opening of calcium channels involves pertussis toxin-sensitive G proteins and activation of phospholipase C and protein kinase C in fibroblasts and lymphocytes (21,38). Studies by Kamisato and colleagues (39,40) additionally revealed that the EBP-dependent chemotactic response of macrophages to elastin-derived peptides also involves FIG.…”
mentioning
confidence: 87%
“…We, and others, show that interaction between elastin-derived peptides and EBP residing on the surface of several cell types results in a rapid and transient increase in free intracellular Ca 2ϩ (18,36) and that the EBP-mediated opening of calcium channels involves pertussis toxin-sensitive G proteins and activation of phospholipase C and protein kinase C in fibroblasts and lymphocytes (21,38). Studies by Kamisato and colleagues (39,40) additionally revealed that the EBP-dependent chemotactic response of macrophages to elastin-derived peptides also involves FIG.…”
mentioning
confidence: 87%
“…A link between elastin and nitric oxide production was revealed when contracted aortic rings showed endothelium-dependent vasodilation following treatment with κ-elastin peptide and tropoelastin [28]. This effect diminished in response to treatment with laminin and lactose, which implicated the surface receptor, elastin binding protein which in turn leads to increased intracellular calcium [6].…”
Section: Discussionmentioning
confidence: 99%
“…Можна припу-стити, що поліморфізм 16-го екзону впливає на чутливість еластину судинної стінки до еластолізу. Як відомо, пептиди еластину, що утворюються внаслідок цього, взаємодіють із еластинламініновими рецепторами ен-дотеліальних та гладеньком'язових клітин судинної стінки, стимулюючи синтез проста-гландинів і продукцію NO із розвитком до-зозалежної вазодилатації [21]. З іншого боку, на фоні активації еластолізу відбувається деградація еластину судинної стінки, підви-щується обмін еластину (на це вказує зро-стання в крові вмісту еластинових пептидів), спостерігається ремоделювання судинної стінки, що асоціюється із збільшенням її ригідності та вищим ризиком ангіопатій у хворих на ЦД 1-го типу [19].…”
Section: результати та їх обговоренняunclassified